2012
DOI: 10.1093/treephys/tps069
|View full text |Cite
|
Sign up to set email alerts
|

The diversification of terpene emissions in Mediterranean oaks: lessons from a study of Quercus suber, Quercus canariensis and its hybrid Quercus afares

Abstract: Interspecific gene flow is common in oaks. In the Mediterranean, this process produced geographical differentiations and new species, which may have contributed to the diversification of the production of volatile terpenes in the oak species of this region. The endemic North African deciduous oak Quercus afares (Pomel) is considered to be a stabilized hybrid between the evergreen Quercus suber (L.) and the deciduous Quercus canariensis (Willd.), presumably being monoterpene and isoprene emitters, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…But we estimated an emission factor of 35.6 ± 5.5 µg g −1 h −1 , confirming more recent literature showing typical summertime values of 10-43 µg g −1 h −1 (Staudt et al, 2004;Pio et al, 2005;Staudt et al, 2008). A further oak species, Quercus afares, was found to emit high quantities of monoterpenes and low amounts of isoprene (see also Welter et al, 2012). Furthermore, we classified Ficus carica and Spartium junceum as non-monoterpene emitters contrasting earlier reports (Benjamin and Winer, 1998;Pio et al, 1993).…”
Section: A Bracho-nunez Et Al: Leaf Level Emissions Of Volatile Orgsupporting
confidence: 90%
“…But we estimated an emission factor of 35.6 ± 5.5 µg g −1 h −1 , confirming more recent literature showing typical summertime values of 10-43 µg g −1 h −1 (Staudt et al, 2004;Pio et al, 2005;Staudt et al, 2008). A further oak species, Quercus afares, was found to emit high quantities of monoterpenes and low amounts of isoprene (see also Welter et al, 2012). Furthermore, we classified Ficus carica and Spartium junceum as non-monoterpene emitters contrasting earlier reports (Benjamin and Winer, 1998;Pio et al, 1993).…”
Section: A Bracho-nunez Et Al: Leaf Level Emissions Of Volatile Orgsupporting
confidence: 90%
“…Compared to carotenoids, which are essential and conserved in higher plants49, non-essential isoprenoids are highly variable across species50 and within species5152. This variability was reflected by the observed provenance-specific differences in monoterpene pool sizes, which exceeded the observed variations in essential isoprenoids by far (Figs 3F and 8A).…”
Section: Discussionmentioning
confidence: 89%
“…This procedure is commonly used when accessibility to large and tall natural trees with the cuvette system without branch disturbance is difficult or impossible (e.g., Affek and Yakir, 2002;Geron et al, 2006;Harley et al, 1998;Helmig et al, 1999;Klinger et al, 1998;Monson et al, 2007). On the basis of our experiences, measuring cut branches does not alter terpene emissions (Ghirardo et al, 2011;Welter et al, 2012) and lipoxygenase-derived compound emissions in distant foliage (e.g., Ghirardo et al, 2011) considerably for several hours. This agrees with Loreto et al (2006), who showed that except for a small amount of acetaldehyde, no other BVOCs were emitted from broadleaf plant species when the mechanical wounding (cutting) is remotely located.…”
Section: Plant Species Measuredmentioning
confidence: 89%